Translanguaging Practices in Indonesia’s Teaching Practice Program: Strategies and Pedagogical Functions at Junior High School - Restiana, Vionita Iken; Sakhiyya, Zulfa (Journal of English Language and Education, 2026)
Translanguaging enables educators and learners to adapt in the learning process of English as a Foreign Language (EFL) by utilizing their entire linguistic repertoire. This qualitative case study aims to analyze the use of translanguaging focusing on strategies and pedagogical function by three pre-service teachers during their teaching practice (PPL) in junior high schools. Data were collected through semi structured interviews and video observations, which were then analyzed using qualitative case study analysis. The results show that teachers often use various languages such as Indonesia and Javanese, semiotics resources also used to encourage learning. Another strategy that found is the use of simple translation (translative) method and complex translating (interwoven) method. In addition, there are pedagogical functions of translanguaging that include class management, improving student understanding and participation, explaining concepts of the material and instructions. These results show the importance of translanguaging practices by pre-service teachers to improve and strengthen student learning in the EFL context.